Reduction of Occupational Risks through the Application of an SGSST based on the ISO 45001:2018 Standard in the Company ForliS.A.C. - Cuevas-Cardenas, Zuhey; Rodriguez-Mendoza, Julio; Evangelista-Guia, Wilfredo; Alarcon-Ventura, Katicsa; Villalobos-Meneses, Bertha; Zevallos-Vera, Erika; Salazar-Sandoval, Fredy (LACCEI, 2025)
The objective of this research is to demonstrate, through the Application of an Occupational Health and Safety Management System based on the ISO 45001:2018 Standard, the reduction of occupational risks in the company Forli S.A.C. This is because, in this organization, whose function is the manufacture of rest products, disorder in the area, inadequate facilities, work accidents, lack of OSH culture have been evident; as well as, lack of identification of risks and dangers. Therefore, the methodology applied with a pre-experimental design has been used, through the use of descriptive statistics for data analysis and confirmation of general and particular hypotheses. After carrying out the Shapiro Wilk Test, with the objective of examining the data obtained from the 16 accident records, the Wilcoxon test was used to establish the validity of our hypotheses. Achieving significance values less than 0.05, concluding the validity of the initially proposed hypothesis. In this way, a 96.28% reduction in the accident rate and a 93.64% reduction in the accident frequency rate was recorded.